The structure of the modern river-valley system of the Upper Prut - Kosteniuk, Liudmyla; Костенюк, Людмила Володимирівна (Academic Society of Michal Baludansky, 2017)
In the following work, we formulate the theoretical-methodological and methodic foundations for the research of the river-bad formation lows in the river system of the Upper Prut. The method of the river-bed investigation and geomorphological division of the modern river-valley systems into characteristic components is suggested and tested with the usage of the method of the geo-informational systems. Also, the main parts of the modern river-valley system of the Upper Prut are marked and described.
Структура сучасної системи руслоформування у річковій системі Верхнього Пруту
Keywords: river-bad processes; GIS methods; river-valley system